Analysis of FGF20‐regulated genes in organ of Corti progenitors by translating ribosome affinity purification. Issue 10 (10th July 2020) - Yang, Lu M.; Stout, Lisa; Rauchman, Michael; Ornitz, David M.
Abstract: Background: Understanding the mechanisms that regulate hair cell (HC) differentiation in the organ of Corti (OC) is essential to designing genetic therapies for hearing loss due to HC loss or damage. We have previously identified Fibroblast Growth Factor 20 (FGF20) as having a key role in HC and supporting cell differentiation in the mouse OC. To investigate the genetic landscape regulated by FGF20 signaling in OC progenitors, we employ Translating Ribosome Affinity Purification combined with Next Generation RNA Sequencing (TRAPseq) in the Fgf20 lineage. Results: We show that TRAPseq targeting OC progenitors effectively enriched for RNA from this rare cell population. TRAPseq identified differentially expressed genes (DEGs) downstream of FGF20, including Etv4, Etv5, Etv1, Dusp6, Hey1, Hey2, Heyl, Tectb, Fat3, Cpxm2, Sall1, Sall3, and cell cycle regulators such as Cdc20 . Analysis of Cdc20 conditional‐null mice identified decreased cochlea length, while analysis of Sall1 ‐null and Sall1‐ΔZn2‐10 mice, which harbor a mutation that causes Townes‐Brocks syndrome, identified a decrease in outer hair cell number. Conclusions: We present two datasets: genes with enriched expression in OC progenitors, and DEGs downstream of FGF20 in the embryonic day 14.5 cochlea. We validate select DEGs via in situ hybridization and in vivo functional studies in mice. Key Findings: Translating Ribosome Affinity Purification (TRAP) targeting the Fgf20‐Cre lineage enriched for organ of Corti progenitor RNA. TRAP combined with RNAseq (TRAPseq) identified genes downstream of FGF20 during organ of Corti differentiation. FGF20 regulates Sall1, gene implicated in human sensorineural hearing loss. Sall1 mutant mice exhibit a decrease in the number of organ of Corti outer hair cells.